Intravesical bacillus Calmette–Guérin-induced myopathy presenting as rhabdomyolysis: a case report - Chae Hun Lee; Byeong Joo Choi; Jung Hun Kim; Tae Woong Yang; Gi Jeong Kim; Ha Young Shin; Se Hoon Kim; Seung Woo Kim (Journal of Yeungnam Medical Science, 2023)
Intravesical bacillus Calmette–Guérin (BCG) instillation is an adjuvant treatment for non–muscle-invasive urinary bladder cancer. Although most complications associated with BCG immunotherapy are mild and self-limiting, rare albeit serious complications have been reported. Only a few cases of BCG-related rhabdomyolysis have been reported. In this study, we present the case of a 72-year-old woman who developed severe weakness and hyperCKemia following intravesical BCG instillation. A muscle biopsy was performed, and a diagnosis of drug-induced myopathy was made.